NOTAS SOBRE ESTÉTICA PEDAGÓGICA E CORPO MASCULINO DOCENTE MARGINAL - Gladys Mary Ghizoni Teive; Rogério Machado Rosa (Universidade do Oeste de Santa Catarina, 2012)
This text presents the development of a study at master's level in which we seek to mapthe ways in which secondary school teachers, who do not form part of the culturallyhegemonic domains of the body and of masculinity, build a hybrid masculinity for themselves,outside the commonplace. We emphasize the process of the construction ofa marginal-masculinity-corporality, and its intimate connection with the vicissitudesdifficulties of teaching practice. We use excerpts from teachers' testimonies, obtainedthrough interviews, to discuss the complex imbrication of affective relationships in/of teaching practice and the creation of vanishing points which delineate bodies andmasculinities that are provisional, irregular, profane and perpetually coming-into--being: "artisty in itself". The pedagogical relationship and its development is thoughtof as a potentializing space for the production of heterotopias, the interplay ofcreative forces which brings together random combinations and renews modes beingin the world, or in other words, new aesthetics of existence.